Covalent immobilization of phenolic antioxidant on Ethylene copolymers: An efficient approach toward enhanced long-term stabilization of polypropylene. (8th November 2016) - Manteghi, Amin; Ahmadi, Shervin; Arabi, Hassan
Abstract: In order to prevent the loss of antioxidant from polymer matrix and increase the efficiency of free radical scavenging, a facile approach to prepare macromolecular-bound antioxidants based on copolymers pre-functionalized with hydroxyl side chains is discussed. Stabilizers are effectively synthesized through esterification of 3-(3, 5-di- tert -butyl-4-hydroxyphenyl) propionic acid with hydrolysed ethylene vinyl acetate (EVAl) and ethylene-1-octene copolymer grafted with long-chain monomers bearing hydroxyl groups (POE-H). The structure and composition of functionalized copolymers (EVOAP and POE-A) are followed using 1 H NMR, FT-IR and GPC. The macromolecular stabilizers exhibit outstanding thermal degradation and oxidation stability in comparison with commercial corresponding copolymers (EVA and POE) and stabilized polypropylene products based on TGA and OIT results. In addition, binary blends of PP/EVOAP and PP/POE-A are assessed for short and long-term thermal stability and resistance to antioxidant extraction with ethanol. Compared to commercial PP, binary blends showed significantly lower amounts of leached stabilizers and the radical scavenging efficiency remained unchanged. In addition to efficiency of macromolecular-bound phenolic stabilizers in prevention of antioxidant mobility and loss due to extraction and volatilization, the compatibilizing effect of functionalized ethylene copolymers, which resemble the backbone structure of polyolefins, results in homogeneous distribution of immobilized phenolic moieties in non-polar polymer matrix. Graphical abstract: Highlights: Phenolic antioxidant was immobilized on hydroxyl functionalized ethylene copolymer. Hydroxyl containing POE was prepared via melt radical grafting of long-chain monomer. Macromolecular stabilizers reveal enhanced thermo-oxidation stability. EVOA and POE-A prevent antioxidant loss from PP and provide long-term stabilization.